ESSENTIAL OILS IN CULTURAL HERITAGE CONSERVATION IN INDONESIA: A METHOD, MATERIAL COMPOSITION, AND RESEARCH DEVELOPMENT - Rofi Surya Aryanto (Kalyanamitra: Journal of Archaeological Resource Management, 2026)
Applied archaeological research, especially conservation in Indonesia, is really needed, considering that it is still relatively new, and historically, cultural heritage maintenance techniques have still focused on chemicals. The emergence of essential oils as conservation materials initiated by the Borobudur Conservation Center agency was the forerunner to the birth of scientific developments and research regarding care materials for cultural heritage and the use of local plants as inhibitors of the growth of biodeteriorating agents. The data in this paper focuses on a review of several studies that used local plants as conservation materials for cultural heritage made from brick, stone, and paper. Reflection in this developing long-term research is needed to create a protocol to use essential oils as a conservation material in every cultural heritage, which is a different material